Patient Satisfaction in a Safety Net Urology Clinic. Issue 2 (27th March 2021) - Butler, Christi; Baskin, Avi S.; Mmonu, Nnenaya A.; Cohen, Andrew J.; Patino, German; Li, Yi; Enriquez, Anthony; Ramstein, Joris; Breyer, Benjamin N.
Abstract: Introduction: Patient satisfaction has become an important metric in medicine. In this study, we aim to identify modifiable factors contributing toward poor satisfaction amongst patients in a safety net urology clinic. We hypothesize that wait times and long distances traveled to clinic will have the largest contribution toward negative patient experiences. Methods: We conducted a cross-sectional study of adult patients presenting to the urology clinic at Zuckerberg San Francisco General Hospital. Participants completed a survey using the RAND Patient Satisfaction Questionnaire-18 after their clinic visit. Associations among demographic factors, wait times, use of a translator and satisfaction were examined. Results: Two hundred patients, 19 to 90 years old (median age 62), were enrolled. Overall, 65% of patients were satisfied with their experience in our clinic. Our results demonstrated a significant association among race, language and overall satisfaction scores (p=0.009 and p=0.003, respectively). Multivariable analysis showed that those who waited more than an hour to see a physician were less satisfied compared with those who waited less than 15 minutes (OR 0.25, 95% CI 0.08–0.74). Similarly, those who used a translator were less satisfied than those who did not use a translator (OR 0.29, 95% CI 0.08–1.01). Conclusions: In a safety net urology clinic, language differences and wait times may contribute to poor patient satisfaction. Future efforts toward improving language interpreter functionality and decreasing patient wait times will likely improve patient satisfaction.